Evaluación de la restauración pasiva en tres estadios sucesionales de la vegetación en la Reserva Natural El Cristal, Loja, Ecuador - Contento Yunga, Cristian Geovanny (2025)
There are large land areas in Ecuador which have been disturbed by anthropogenic activities, in order to recover these ecosystems, restoration actions have been established and these must be monitored and evaluated. This research was carried out at El Cristal Natural Reserve (RNEC), with the objective of evaluating passive restoration in three successional vegetation stages through a survey of diversity, structure and floristic composition. Three successional stages were studied, they were differentiated by the abandonment time: 10-20, 20-30 and 30-40 years and the reference ecosystem. In each successional stage, three 20 x 20 m plots were established, recording individuals with DAP higher than 5 cm, corresponding to the stem category; within these, 5 subplots of 5 x 5 m were nested for the latizal category, where individuals less than 5 cm of DAP and up to 1.50 m high were recorded; and, at the same time, within these, 5 subplots of 1 x 1 m were established for the sapling category, recording individuals up to 1.50 m in height. The diversity, structure and floristic composition were determined, the structural parameters of the vegetation and diversity indices were calculated; and, the succession stages were compared using the Sorensen similarity index. The floristic composition was; 14 species from 12 genera and 12 families in stage one; 15 species from 14 genera and 14 families in stage two; 20 species, from 19 genera and 18 families for stage three and 26 species within 24 genera and 23 families for the reference ecosystem. Regarding diversity, stage one with a Shannon index of 0.74 presents low species diversity and for Pielow with 0, 33, it is slightly heterogeneous in terms of abundance. Stage two and three are moderately similar related to diversity with numbers of 1.73 and 1.96 respectively, while the reference ecosystem registers numbers of 2.80 it is classified as high diversity. There is floristic similarity between stages three and four with 69.57% and 16 species in common. In conclusion, the vegetation recovery through natural succession processes is an important in situ restoration strategy, because the appearance and establishment of typical species are observed and they will lead to the formation of similar ecosystems to the reference systems in the future.